Perception of Consequences of Rape Among Students in Adeyemi College of Education, Ondo - Soetan, Margaret Kehinde; Ademikanra, Adedayo O. (Teaching, Learning, and Development, 2026)
This study examined perception of consequences of rape among tertiary institution students. A survey research design was adopted for this study. The population comprised all students in Adeyemi College of Education, Ondo. The sample consisted of two hundred and fifty (250) students randomly selected from the college. Structured questionnaire was used to collect data for the study. Reliability of the instrument was ascertained using Cronbach’s Alpha statistics which yielded a coefficient of 0.85. Data were analysed using mean, ranking and t-test. The results showed that consequences of rape are emotional disturbance, depressive symptoms, pregnancy and sleeping difficulties among others. It was also found that family type and marital status have significant influence on perception of consequences of rape among tertiary institution students (t = 7.192, p<0.05 and t = 3.185, p<0.05) respectively while gender and religion do not (t =5.183, p>0.05 and t = 6.030, p>0.05) respectively. It was therefore recommended that brief cognitive – behavioural programme should be administered shortly after rape to hasten the rate of improvement of psychological damage arising from trauma.